Letter: complications of percutaneous liver biopsy with Klatskin needles—methodological issues. Issue 3 (4th July 2017) - Ayubi, E.; Sullman, M. J. M.; Safiri, S.
Abstract : Linked Content This article is linked to Takyar et al, and Takyar and Koh papers. To view these articles visithttps://doi.org/10.1111/apt.13939 andhttps://doi.org/10.1111/apt.14170 .